2013
DOI: 10.5539/ijbm.v8n14p168
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Auditing and the Provision of Non-Audit Services: Case Study in Libya

Abstract: This paper examines whether non audit service are associated with audit quality. In relation to the impact of non-audit service on audit quality, the provision of NAS to audit clients was found to provide auditors with greater experience of the client's industry and greater access to the client's accounting system. Additionally, such an arrangement was considered to enhance audit quality, but simultaneously it was also believed that a separation of NAS from audit services was desirable since auditors are perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…This result indicates that respondents support the idea that audit quality is enhanced and auditor objectivity is improved if NAS were provided by the auditor. The above result is consistent with most previous studies (Hartley & Ross, 1972;Goldman & Barlev, 1974;Glezen & Millar, 1985;Gul, 1989;Wallman, 1996;Antle et al, 1997;Arrunada, 1999;Sawan et al, 2013). These results can be justified since the auditor's awareness and knowledge of the client's company would be improved by the provision of NAS, leading to increase objectivity and independence (Goldman & Barlev, 1974); that providing NAS would lead to improve audit quality (Antle et al, 1997); or that the auditor provision of NAS to their audit clients decreases total costs, increase technical competence and motivates more intense competition (Arrunada, 1999).…”
Section: The Overall Samplesupporting
confidence: 93%
See 1 more Smart Citation
“…This result indicates that respondents support the idea that audit quality is enhanced and auditor objectivity is improved if NAS were provided by the auditor. The above result is consistent with most previous studies (Hartley & Ross, 1972;Goldman & Barlev, 1974;Glezen & Millar, 1985;Gul, 1989;Wallman, 1996;Antle et al, 1997;Arrunada, 1999;Sawan et al, 2013). These results can be justified since the auditor's awareness and knowledge of the client's company would be improved by the provision of NAS, leading to increase objectivity and independence (Goldman & Barlev, 1974); that providing NAS would lead to improve audit quality (Antle et al, 1997); or that the auditor provision of NAS to their audit clients decreases total costs, increase technical competence and motivates more intense competition (Arrunada, 1999).…”
Section: The Overall Samplesupporting
confidence: 93%
“…Palmrose and Saul (2001) indicated that the arrangements in which audit firms delivered, both audit and NAS, the NAS has a supportive influence on the effectiveness of the audit. Sawan, Alzeban and Hamuda (2013) found that the provision of NAS improves audit quality. Furthermore, some forensic auditors testified that specific types of frauds might have been eliminated or identified if NAS had been delivered to the audit client or if well communication had ensued between NAS personnel and the audit engagement team (Joshi et al, 2007).…”
Section: Audit Quality Is Improved and Enhanced By Rendering Nasmentioning
confidence: 99%